Vides en els marges a la València del segle XV. - PEIRATS, ANNA (Scripta, 2024)
This article focuses on the description of the other look of Valencia in the fifteenth century, that of social marginalisation, which could be manifested by the exercise of various immoral offices. The following pages describe two female groups, particularly treated as vile: those of healers, sorcerers, and witches, whose strength was considered to be of demonic origin, and prostitutes, dedicated to covering a «minor evil» in society, but viewed as indignant by society due to the practical exercise of their profession.